Trajectory simulation of multi-body parachute system for airdrop-capable UAVs based on fluid-structure interaction - Hanxu Guo; Ziang Gao; Zijian Zhu; Miao Zhang; Jian Zhang (PLoS ONE, 2026)
Due to their demonstrated advantages of precision, efficiency, and low cost in disaster relief and commercial logistics, airdrop-capable unmanned aerial vehicle (UAV) are rapidly becoming pivotal tools in modern delivery systems. This paper proposes a novel airdrop-capable UAV with foldable wings. To address the requirements for high-precision deployment and parachute cut-off, a 10-degree-of-freedom (10-DOF) multibody dynamics model of the parachute-UAV system is established based on Kane’s equations. The solution process incorporates sixth-order vibration equations to characterize the system’s rigid-flexible coupling effects, precisely capturing the motion trajectories under varying initial deployment parameters (initial velocity, parachute diameter). To comparatively analyze the trajectory curves derived from fluid-structure interaction (FSI) simulation and to validate the model’s effectiveness, this paper constructs a co-simulation framework. This framework couples Gamma-Theta transition model-based FSI with LS-DYNA to simulate the airdrop dynamics across multiple operating conditions. This study acquires the parachute jettison coordinates of an airdrop UAV under varying deployment parameters, elucidating their parametric dynamic coupling on airdrop trajectories and separation point selection methodology. These findings establish both theoretical principles and technical frameworks for precision guidance and flight trajectory control.